The data registry of the European Competence Network on Mastocytosis (ECNM): set Up, projects, and perspectives - Valent, Peter; Oude Elberink, Joanna N. G.; Gorska, Aleksandra; Lange, Magdalena; Zanotti, Roberta; van Anrooij, Björn; Bonifacio, Massimiliano; Bonadonna, Patrizia; Gleixner, Karoline V.; Hadzijusufovic, Emir; Perkins, Cecelia; Hartmann, Karin; et al. (The journal of allergy and clinical immunology. In practice, 2018)
Mastocytosis is a unique hematologic neoplasm with complex biology and pathology and a variable clinical course. The disease can essentially be divided into cutaneous mastocytosis (CM) and systemic mastocytosis (SM). In adults, SM is diagnosed in most cases and manifests as either indolent or advanced disease. Patients with advanced SM have an unfavorable prognosis with reduced survival. However, so far, little is known about the prevalence of various categories of SM and about prognostic factors. In an attempt to learn more about the behavior and evolution of various forms of CM and SM, the European Competence Network on Mastocytosis (ECNM) initiated a mastocytosis registry in 2012. In this article, the set up and start phase of this registry are described. Until 2018, more than 3000 patients from 12 countries and 25 centers have been enrolled. In a majority of all patients, robust follow-up data and relevant clinical end points are available. Using this data set, a series of registry projects have been launched, with the aim to validate previously identified diagnostic and prognostic variables and to identify new disease-related and patient-related parameters in various forms of mastocytosis. Moreover, the core data set of the registry will be useful to establish multiparametric scoring systems through which prognostication and individualized management of patients with mastocytosis should improve in the foreseeable future.
Gesehen am 28.02.2020